2014
DOI: 10.1016/j.jagp.2012.12.217
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Cognitive Decline in the Baltimore Epidemiologic Catchment Area Follow-up Study

Abstract: Objective To determine the association between personality domains and 11-year cognitive decline in a sample from a population-based study. Method Data from Waves 3 (1993–1996) and 4 (2003–2004) of the Baltimore cohort of the Epidemiologic Catchment Area (ECA) study were used for analyses. The sample included 561 adults (mean age ±SD = 45.2 ±10.78 years) who completed the NEO Personality Inventory-Revised (NEO PI-R) prior to Wave 4. Participants also completed the Mini-Mental State Examination (MMSE) and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 36 publications
4
32
1
2
Order By: Relevance
“…Although exploratory, our findings suggest that conscientiousness may be a protective resource for brain aging, being associated with higher within‐FPN connectivity, which is otherwise expected to decrease as a function of age (Campbell, Grady, Ng, & Hasher, ). Our result is in line with several observations that show conscientiousness as a predictor for academic or occupational success, healthy lifestyle, reduced cognitive decline, and longevity (Bogg & Roberts, ; Costa, Weiss, Duberstein, Friedman, & Siegler, ; Hock et al, ; Noftle & Robins, ; Ozer & Benet‐Martínez, ; Sutin & Terracciano, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although exploratory, our findings suggest that conscientiousness may be a protective resource for brain aging, being associated with higher within‐FPN connectivity, which is otherwise expected to decrease as a function of age (Campbell, Grady, Ng, & Hasher, ). Our result is in line with several observations that show conscientiousness as a predictor for academic or occupational success, healthy lifestyle, reduced cognitive decline, and longevity (Bogg & Roberts, ; Costa, Weiss, Duberstein, Friedman, & Siegler, ; Hock et al, ; Noftle & Robins, ; Ozer & Benet‐Martínez, ; Sutin & Terracciano, ).…”
Section: Discussionsupporting
confidence: 92%
“…Evidence indicates that personality traits, particularly conscientiousness, neuroticism, and openness, are associated with general health, longevity, cognitive performance (Chapman, Roberts, & Duberstein, ; Curtis, Windsor, & Soubelet, ), and dementia risk (Chapman et al, ; Terracciano & Sutin, ). Conscientiousness has been associated with reduced cognitive decline, while neuroticism has been associated with greater decline (Caselli et al, ; Hock et al, ; Luchetti, Terracciano, Stephan, & Sutin, ). Similarly, individuals who scored lower on conscientiousness and higher on neuroticism shower greater risk for development of Alzheimer's Disease (AD; Terracciano et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the same line, the Baltimore Epidemiologic Catchment Area study indicated a small but still significant negative association between neuroticism and MMSE scores. Higher levels of Consciousness were associated with a slight improvement in general cognitive function measures in this cohort [44]. Our data do not confirm the negative effect of higher Neuroticism levels on cognitive fate in normal aging.…”
Section: Discussioncontrasting
confidence: 63%
“…A high neuroticism score is associated with fear, sadness, embarrassment, guilt, and anger (McCrae and Costa, 2010). High neuroticism has been linked to a steeper cognitive decline (Chapman et al, 2012;Hock et al, 2014;Luchetti et al, 2015), poorer overall cognition (Boyle et al, 2010), and an increased risk of dementia (Duberstein et al, 2011). Yet, a link between neuroticism and cognitive decline was not confirmed by others (Wetherell et al, 2002;Jelicic et al, 2003).…”
Section: Introductionmentioning
confidence: 99%